Essentials Of Marketing: A Global Managerial Approach - William D.Perreault, E. Jerome McCarthy (Mc Graw Hill, 2006)
This book is about marketing and marketing strategy planning,and at it essence, marketing strategy planning is about figuring out how to do a superior job of satisfying customer